2022
DOI: 10.1007/s00520-022-07208-x
|View full text |Cite
|
Sign up to set email alerts
|

Fall predictors in hospitalized patients living with cancer: a case–control study

Abstract: Purposeto identify fall predictors and develop an assessment tool to be used for screening hospitalized cancer patients at risk for fall. Methodsa retrospective case-control study was conducted in 2018 at a cancer center in Northern Italy. The study participants were 448 adult cancer patients admitted to the oncology ward from 2009 to 2013. The cases group consisted of 112 patients presenting at least one fall, while controls were randomly chosen by matching each case for age, sex and admission period with thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This scale has strong operability and high practicability in all adult patients in the clinic. Studies have shown that its sensitivity and specificity for predicting fall-induced injuries are 100% and 65.9%, respectively [7][8][9][10]. However, this scale has not been validated in patients with AMI after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…This scale has strong operability and high practicability in all adult patients in the clinic. Studies have shown that its sensitivity and specificity for predicting fall-induced injuries are 100% and 65.9%, respectively [7][8][9][10]. However, this scale has not been validated in patients with AMI after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient falls detrimentally impact patients, leading to extended hospital stays and distress among families and caregivers [1][2][3][4][5]. Studies reflect a varying incidence rate of such falls, with 250,000 annually in England and Wales alone [1], and evidence showing 7.5% of patients experience at least 1 fall during hospitalization [2].…”
Section: Introductionmentioning
confidence: 99%